Mycobacterial skin infection - Gardini, Giulia; Gregori, Natalia; Matteelli, Alberto; Castelli, Francesco (Current opinion in infectious diseases, 2022)
The aim of this article is to review the most recent evidences concerning mycobacterial skin infections, limiting the period of literature research to 2020--2021. Mycobacterial skin infections include a heterogeneous group of cutaneous diseases.Cutaneous tuberculosis is usually the result of hematogenous dissemination or spread from underlying foci and it must be distinguished from tuberculids, resulting from the immunological reaction to Mycobacterium tuberculosis antigens. Leprosy prevalence was drastically reduced after introduction of multidrug therapy in the 1980 s, but cases are still reported due to underdiagnosis, and animal and environmental reservoirs. Recent advances concentrate in the diagnostic field. Specific guidelines for the treatment of nontuberculous mycobacteria skin infections are missing and surgical procedures may be required. Prognosis is better as compared to nontuberculous mycobacteria lung disease. Rapid laboratory-confirmed diagnosis of Buruli ulcer may be achieved by the IS2404 PCR. Among new drugs, telacebec is promising in terms of potency, shorter duration and tolerability in animal studies. A clinical trial in humans is planned. Mycobacterial cutaneous lesions are nonpathognomonic and clinical suspicion must be confirmed by culture or molecular detection. Long-course multidrug treatment is required based on susceptibility tests. Surgical intervention may also be required. Rehabilitation and psychosocial support reduce long-term physical and mental consequences mostly in Buruli ulcer and leprosy.